Development of Research & Development Dashboard For an University - Subrahmanyam, Kodukula; Ketha, Tirumuru; Balakrishna, Salichemaladevarajulu; Naga Manoj Kumar, Telaprolu (International Journal of Engineering and Technology, 2018)
An information dashboard is a data association gadget that ostensibly tracks, displays and demonstrates the principle key execution markers (KPI) and key information focuses to screen the soundness of a business, university, office or particular process. They are versatile to meet the specific needs of an office and company or an university. A dashboard interfaces with our documents, attachments, services and API's, yet at first look shows this information as tables and also used to monitor and track various data. As constant checking decreases the hours of breaking down an information dashboard is the most proficient approach to track numerous information. In Research and progression work is facilitated towards the innovation, introduction, and development and advancement of products and processes. In this project we are going to develop a framework for R&D of a University in this we are mainly focusing on the Academic Research, sponsored & Internal Funding Research, Consultancy, center of Excellence, Innovation Incubation & Entrepreneurship and Extramural.This R&D Dashboard is utilized for web based enlisting for patents, copyrights, licenses, copyrights, productions in meetings, sorting out gatherings, seminars and workshops. This Dashboard was developed, utilizing Windows-based Microsoft excel, VISUAL BASIC and back end is Microsoft Access Database. The VISUAL BASIC has easy to use pull down menus and toolbars for different analysis.Â